1998
DOI: 10.1088/0963-9659/7/5/004
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We present an approach for describing the properties of a quasi-monochromatic, beam-like field that is both partially polarized and partially coherent from the spatial standpoint. It is based on the use of a single 2 × 2 matrix, called the beam coherence-polarization matrix, whose elements have the form of mutual intensities. This approach, which can be viewed as an approximate form of Wolf's general tensorial theory of coherence, appears to be very simple, yet it is able to cover significant aspects of the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
46
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(48 citation statements)
references
References 40 publications
2
46
0
Order By: Relevance
“…5 In fact, a single 2 3 2 matrix, called a beam coherencepolarization (BCP) matrix, is suff icient to yield a complete account of the second-order statistical properties of the f ield. 3 In scalar coherence theory, the van Cittert-Zernike theorem is a fundamental tool for studying the propagation processes of partially coherent fields. 5,6 Moreover, several partially coherent beams are generated starting from a primary spatially incoherent source.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5 In fact, a single 2 3 2 matrix, called a beam coherencepolarization (BCP) matrix, is suff icient to yield a complete account of the second-order statistical properties of the f ield. 3 In scalar coherence theory, the van Cittert-Zernike theorem is a fundamental tool for studying the propagation processes of partially coherent fields. 5,6 Moreover, several partially coherent beams are generated starting from a primary spatially incoherent source.…”
mentioning
confidence: 99%
“…3 Since the f ield specified by Eqs. (8) and (9) is linearly polarized, there is a perfect correlation between any two f ield components at a typical source point.…”
mentioning
confidence: 99%
“…The seminal work on the subject was published by James [7], who showed that the degree of polarization of light beams may change upon propagation, depending on the spatial correlation properties of the light beam. Such an intrinsic connection between spatial coherence and partial polarization has been discussed in numerous later works (see, for example, [8][9][10][11][12]). …”
mentioning
confidence: 71%
“…However, since the formulation of the unified theory of coherence and polarization [10][11][12], several studies have been devoted to the question of how the HBT effect in random electromagnetic beams can be analyzed [13][14][15][16][17]. It is well known that the fundamental properties of these beams, such as their spectrum, degree of polarization, state of polarization, and degree of coherence, can all change significantly on propagation, even when the propagation is through free space [18][19][20][21][22][23][24]. However, until now a detailed investigation of the evolution of the HBT effect in random electromagnetic beams has been lacking.…”
mentioning
confidence: 99%